Sustained FXN expression in dorsal root ganglia from a nonreplicative genomic HSV‐1 vector. (19th November 2017) - Ventosa, Maria; Wu, Zetang; Lim, Filip
Abstract: Background: Friedreich's ataxia (FA) is an autosomal recessive neurodegenerative disease caused by mutations in the frataxin gene ( FXN ), which lead to reduced levels of the essential mitochondrial protein frataxin. Currently, there is no effective cure. Methods: With the aim of developing a gene therapy for FA neuropathology, we describe the construction and preliminary characterization of a high‐capacity nonreplicative genomic herpes simplex virus type 1 vector (H24B‐FXNlac vector) carrying a reduced version of the human FXN genomic locus, comprising the 5‐kb promoter and the FXN cDNA with the inclusion of intron 1. Results: We show that the transgene cassette contains the elements necessary to preserve physiological neuronal regulation of human FXN expression. Transduction of cultured fetal rat dorsal root ganglia neurons with the H24B‐FXNlac vector results in sustained expression of human FXN transcripts and frataxin protein. Rat footpad inoculation with the H24B‐FXNlac vector results in human FXN transgene delivery to the dorsal root ganglia, with expression persisting for at least 1 month. Conclusions: The results of the present study support the feasibility of using this vector for sustained neuronal expression of human frataxin for FA gene therapy.